Revealing the characteristics of Indonesian language test used in the national-standardized school examinations - Ulwatunnisa, Marwah; Retnawati, Heri; Muhardis, Muhardis; Yusron, Eri (REID (Research and Evaluation in Education), 2023)
This study aimed to determine the characteristics of Indonesian language test used in the national standardized school examinations (Ujian Sekolah Berstandar Nasional, USBN). We used the response data of 218 students from a public senior high school in the Special Region of Yogyakarta, Indonesia, to the test consisting of two packages, A and B, in the 2018/2019 academic year to investigate the characteristics of the test and its items. Quantitative analysis using classical test theory (CTT) and one-parameter logistic item response theory (1-PL IRT) model was conducted to investigate the characteristics of the test and its items based on difficulty and discriminating power. The results of the study under the CTT showed that most test items in both package A and package B have difficulty in the easy category and the portion of items in the difficult category is no more than 10%. In addition, while the majority of test items in both test packages demonstrated good discriminating power, package B contained a high number of items with poor discriminating power (47.5%). Under 1-PL IRT, our study results indicated the dominance of items with difficulty level in the moderate category in both test packages. In addition to revealing the difficulty level of the test items, our study showed that the items in the difficult category under CTT and IRT were related to the topics of types of conjunction; spelling, grammar, and sentence structure; job application letter; and observation report text and its structure. The results of this study are expected to contribute to improving the quality of the Indonesian language test and the quality of learning on topics where students have difficulty based on test items in the difficult category.